A Three-Dimensional Consideration of Variant Human Fibrinogens - Everse, Stephen J.; Spraggon, Glen; Doolittle, Russell F. (Thrombosis and Haemostasis, 1998)
Recently reported X-ray structures for large core fragments derived from human fibrinogen and fibrin make it possible to correlate structural and functional anomalies of known genetic variants. Here we examine a variety of amino acid replacements previously reported for hereditary dysfibrinogenemias, most of which are associated with impaired fibrin polymerization. For many of these we have modeled in the mutant amino acid and considered the structural consequences. We have also examined the cases of a small deletion and a large insertion, as well as the impact of substitutions in the GPRPam ligand that was co-crystallized with fragment double-D.